FIGURATIVE LANGUAGES IN ARIANA GRANDE “POSITIONS” ALBUM - A A Ayu Istri Chuk Putri Larassati; Ni Made Verayanti Utami; Ida Ayu Putri Gita Ardiantari (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
The study concerns with the types of figurative language in the song lyric found in ‘Positions’ album by Ariana Grande. The researcher assumed that the figure of speech in the song lyrics are interesting to analyse. The study aims to analyse the types of figurative language in the song lyrics and analyse the meaning that conveys in the song lyric that contains figurative language. This study uses qualitative method to conduct a clear and well-organized description problems that identified. The data were taken from the song lyric and analysed by applying theory types of figurative language by Knickerbocker and Renninger (1963) and theory of meaning by Leech (1981). The study concludes that the figurative language used in the song lyric to deliver a message that the singers want to deliver to the listener of the song, and there are several meanings that conveyed due to understand what the figurative language in the song lyric means. In the Positions album by Ariana Grande found 10 data of figurative language, there are all 1 data of simile, metaphor, personification, synecdoche, metonymy, hyperbole, irony, paradox, dead metaphor and allusion.